2007
DOI: 10.1038/nature05609
|View full text |Cite
|
Sign up to set email alerts
|

A recurrent mutation in PALB2 in Finnish cancer families

Abstract: BRCA1, BRCA2 and other known susceptibility genes account for less than half of the detectable hereditary predisposition to breast cancer. Other relevant genes therefore remain to be discovered. Recently a new BRCA2-binding protein, PALB2, was identified. The BRCA2-PALB2 interaction is crucial for certain key BRCA2 DNA damage response functions as well as its tumour suppression activity. Here we show, by screening for PALB2 mutations in Finland that a frameshift mutation, c.1592delT, is present at significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
394
6
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(438 citation statements)
references
References 16 publications
20
394
6
6
Order By: Relevance
“…2 Mutations in this gene may be associated with familial clustering of PC and BC. [1][2][3][4][5][6][7][8][9][10] Previous studies have shown that PALB2-mutation-positive familial BC (FBC) patients were significantly more likely to have a relative with PC, 5 and that nearly all PALB2-mutation positive familial PC (FPC) families were affected by at least one BC case. 4 Given these findings and the fact that the prevalence of gene mutations varies between different populations, we aimed to determine the prevalence of PALB2 mutations in Dutch cohorts of non-BRCA1/2 FPC patients and of non-BRCA1/2 FBC patients with a personal or family history of PC.…”
Section: Introductionmentioning
confidence: 99%
“…2 Mutations in this gene may be associated with familial clustering of PC and BC. [1][2][3][4][5][6][7][8][9][10] Previous studies have shown that PALB2-mutation-positive familial BC (FBC) patients were significantly more likely to have a relative with PC, 5 and that nearly all PALB2-mutation positive familial PC (FPC) families were affected by at least one BC case. 4 Given these findings and the fact that the prevalence of gene mutations varies between different populations, we aimed to determine the prevalence of PALB2 mutations in Dutch cohorts of non-BRCA1/2 FPC patients and of non-BRCA1/2 FBC patients with a personal or family history of PC.…”
Section: Introductionmentioning
confidence: 99%
“…Limitations of currently used mutation screening methods may explain the low recovery rates [Teugels et al, 2005]. It is generally accepted that mutations in other genes like CHEK2, ATM, PALB2 and BRIP1 could be the cancer predisposing factor in some breast cancer families [Meijers-Heijboer et al, 2002;Erkko et al, 2006;Rahman et al, 2006;Renwick et al, 2006;Seal et al, 2006], but the observed lower penetrance of these mutations and a less obvious cosegregation pattern with the disease suggest that these mutations act according to a polygenic model [Antoniou et al, 2001Ponder, 2001;Pharoah et al, 2002]. The search for additional breast cancer susceptibility genes is still ongoing and candidate genes can be found among those that interact in the same molecular pathways as BRCA1/2.…”
Section: Introductionmentioning
confidence: 99%
“…1). For some of the moderate-penetrance genes, ATM, BRIP1, CHEK2 and PALB2, the data are still limited to single populations [12][13][14][15][16]. For CHEK2*del1100delC and ATM variants the PAF estimates are about 0.5% each; adding up the other CHEK2 variants, BRIP1 and PALB2 mutations the sum PAF would be around 1.5% (Fig.…”
Section: Introductionmentioning
confidence: 99%